Exploring spatial variations and factors associated with childhood stunting in Ethiopia: spatial and multilevel analysis. Issue 1 (December 2016) - Haile, Demewoz; Azage, Muluken; Mola, Tegegn; Rainey, Rochelle
Abstract Background Stunting reflects a failure to receive adequate nutrition over a long period of time. Stunting is associated with adverse functional consequences including poor cognition, low educational performance, low adult wages, and poor reproductive outcomes. The objective of the study was to investigate spatial variations and factors associated with childhood stunting in Ethiopia. Methods This study is a secondary data analysis of the 2011 Ethiopian Demographic and Health Survey (EDHS). A total of 9893 children aged 0–59 months were included in the analysis. The Getis-Ord spatial statistical tool was used to identify high and low hotspots areas of stunting. A multilevel multivariable logistic regression was used to identify factors associated with stunting. Results Statistically significant hotspots of stunting were found in northern parts of the country whereas low hotspots where there was less stunting than expected were found in the central, eastern, and western parts of the country. In the final model of multilevel logistic regression analysis, individual and community level factors accounted for 36.6 % of childhood stunting. Short birth interval [AOR = 1.68; 95%CI: (1.46–1.93)], being male [AOR = 1.20; 95%CI: (1.08–1.33)], and being from a male-headed household [AOR = 1.18; 95 % CI: (1.01–1.38)] were the factors that increased the odds of stunting at the individual level. Children in the age group between 24–35 months were more likely to be stunted than children whose age was less than one year [AOR = 6.61; 95 % CI: (5.17–8.44)]. The odds of stunting among children with severe anemia were higher than children with no anemia [AOR = 3.23; 95%CI: (2.35–4.43)]. Children with mothers who had completed higher education had lower odds of being stunted compared to children whose mothers had no formal education [AOR = 0.42; 95%CI: (0.18–0.94)]. The odds of being stunted were lower among children whose fathers completed higher education [AOR = 0.58; 95%CI: (0.38–0.89)] compared to children whose fathers had no formal education. Children whose mothers who had high a Body Mass Index (BMI) (≥25.0 kg/m2 ) were less likely to be stunted compared with children whose mothers had a normal BMI (18.5 kg/m2 -24.9 kg/m2 )[AOR = 0.69; 95%CI: (0.52–0.90)]. Children from the poorest wealth quintile had higher odds of being stunted compared to children from the richest wealth quintiles [AOR = 1.43; 95 % CI: (1.08–1.88)]. Unavailability of improved latrine facilities and living in the northern parts of the country (Tigray, Affar, Amhara and Benishangul-Gumuzregions) were factors associated with higher odds of stunting from the community-level factors. Conclusion Stunting in children under five years old is not random in Ethiopia, with hotspots of higher stunting in the northern part of Ethiopia. Both individual and community-level factors were significant determinants of childhood stunting. The regions with high hotspots of child stunting should be targeted with additional resources, and the identified factors should be considered for nutritional interventions.